Islam and Modern School Education in Journal Pengasuh: Review of the Kaum Muda - Kaum Tua Dichotomy - Kushimoto, Hiroko (Studia Islamika, 2012)
This study analyzes the articles on education that appeared in a journal titled Pengasuh to discover the ideas on education in early 20th century Malaya. It explores the thinking on education that motivated Islamic leaders to establish modern religious schools called madrasah. The example of the Pengasuh shows that new ideas of Islamic learning that supported the spread of new madrasah had been shared regardless kaum muda – kaum tua dichotomy, contrary to the assumption of previous studies. The main difference between the kaum muda and their opponent kaum tua is their attitude toward knowledge accumulated in the schools of Islamic law. The discussions in the Pengasuh shows strong support for the development of modern Islamic education, without denigrating the old style of Islamic learning.DOI: 10.15408/sdi.v19i2.361